Acoustic Emission Technology for High Power Microwave Radar Tubes - Joshi, Narayan R.; Ramirez, Ayax D.; Russell, Stephen D.; Brock, David W. (IntechOpen, 2019)
This book is intended for all those professionals with interest in developing a basic background in acoustic emission and its use as a non-destructive testing technique. The monitoring of high-power microwave radar tubes is an example of the use of such techniques. This book will also be of interest to those involved in the design, maintenance and procurement of high-power microwave radar tubes. And finally, it is also intended for those students of physics and engineering interested in specializing in acoustics and acoustic techniques.